The Log-Balancedness of Combinatorial Sequences - Zhao, Feng-Zhen (Sarajevo Journal of Mathematics, 2024)
In this paper, we discuss the log-balancedness of combinatorial sequences. We consider operators on sequences that preserve the log-balancedness property. We also give a sufficient condition for the log-balancedness of the product of two sequences. As applications, we prove that some combinatorial sequences are log-balanced. In addition, we discuss the reverse ultra log-concavity of some sequences involving the log-balanced sequence.